ADAPTASI ENAM KELUARGA TERHADAP LINGKUNGAN (STUDI KASUS: PEMUKIMAN DALAM KAWASAN TEMPAT PEMBUANGAN AKHIR (TPA) SUNGAI ANDOK DI KECAMATAN PADANG PANJANG BARAT KOTA PADANG PANJANG) - Anatasya Putri Stevannie; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted in the Sungai Andok landfill West Padang Panjang District, Padang Panjang City with the aim of knowing the factors of the community living in the Sungai Andok landfill and knowing the level of community adaptation in the Sungai Andok landfill area. This study uses descriptive qualitative research methods. Data collection was carried out using interview techniques, direct observation, and documentation. The results of the analysis showed that the factors that caused the six families to settle in the Sungai Andok landfill were due to land ownership, proximity to businesses, and the opening of new job opportunities as scavengers. In an effort to adapt six families in the landfill area, there are two forms of adaptation that are carried out, namely adaptation to comfort and adaptation to health. The six informants who live in the Sungai Andok landfill area feel comfortable because they have lived in the landfill area for a long time, but sometimes the smell and flies caused by the presence of the landfill disturb the comfort. Adaptations to health carried out by the six informants were routinely bathing, eating regularly, always cleaning the yard, always washing hands. By doing this, the six informants thought that they had made efforts to maintain their health while they lived in the landfill area. Keywords: Environmental Adaptation, landfill, Comfort, and Health